Relation of the Plasmapause to the Midlatitude Ionospheric Trough, the Sub‐Auroral Temperature Enhancement and the Distribution of Small‐Scale Field Aligned Currents as Observed in the Magnetosphere by THEMIS, RBSP, and Arase, and in the Topside Ionosphere by Swarm. Issue 3 (24th February 2022) - Heilig, Balázs; Stolle, Claudia; Kervalishvili, Guram; Rauberg, Jan; Miyoshi, Yoshizumi; Tsuchiya, Fuminori; Kumamoto, Atsushi; Kasahara, Yoshiya; Shoji, Masafumi; Nakamura, Satoko; Kitahara, Masahiro; Shinohara, Iku
Abstract: The relation between the plasmapause (PP) and various ionospheric phenomena, such as the midlatitude ionospheric trough (MIT) has been studied for decades. More recently, it was found that the equatorward boundary of small‐scale field‐aligned currents (SSB) and the PP are also closely coupled. In spite of prolonged efforts many details of these relationships, as well as the mechanisms responsible for them remain poorly understood. ESA's Swarm mission in conjunction with magnetospheric missions (RBSP, Arase, and THEMIS) provides an unprecedented opportunity to study these relationships on a global scale and over an extended period. Swarm delivers observations of MIT, the associated sub‐auroral electron temperature enhancement (SETE), as well as SSB, while PP crossings can be inferred from in‐situ magnetospheric electron density measurements. In this study, we use 7 years of Swarm observations and PP positions from 2014 to 2017 to address some of the open questions. We confirm that MIT/SETE and PP are directly coupled, however only in the nighttime. Their correlation remains high after post‐dawn, however, with an increasing, MLT‐dependent time lag. Afternoon MIT observations were found conjugated with a plasmaspheric plume. The correlation between SSB and PP is also high and they intersect each other near MLT midnight. Our results confirm the scenario that the PP is formed on the night side, and propagates to the dayside by co‐rotating with the Earth and suggest that the plasma is transported from the depleted ionospheric/dense plasmaspheric stagnation region also westward/sunward forming the afternoon MIT/narrow plumes, respectively. Key Points: The ionospheric trough and the plasmapause are dynamically coupled between the dusk stagnation region and dawn A local time‐dependent delay was found in the time response of the plasmapause to the changes in the ionospheric trough position after dawn A post‐noon trough was found conjugated with a plasmaspheric plume; the same electric field is believed to be responsible for both